The Innovative Strategies Of The Bumi Hijau Center Foundation In Banyuwangi To Realize The Multi-Development School Program - Arif Nugroho; Jumanah Jumanah; Dewi Setiyowati (Sean Institute, 2024)
This research aims to explore and examine organizational strategies that encourage school development innovation through the implementation of the Multi Development School Program. Focusing on strengthening the theoretical foundations of Development Strategy in the Multi-Development School Program, this study centers on initiatives organized by the Bumi Hijau Center Foundation under the auspices of the Education Providing Organization (POP) Policy approved by the Ministry of Education. Education, Culture, Research and Technology (Kemendikbud Ristek). Methodologically, this research uses a descriptive qualitative approach, involving 18 key informants and additional stakeholders who are closely involved in related issues. Researchers conducted observations, interviews and analysis to obtain the conclusion that the Multi Development School Program (PSMP) has produced positive results through interventions carried out by community organizations (ormas) responsible for POP. This intervention has had a significant impact on teachers, principals, students, parents and the wider community, thereby improving overall school performance. Nonetheless, this study underscores the importance of expanding interventions to achieve broader and more sustainable impacts. The challenges in measuring the impact of specific interventions highlight the need for additional data and information on concrete outcomes, particularly in the areas of educational improvement, increased teacher competency, and positive impacts on teachers and principals.